Assessment of Spatial Soil Erosion Susceptibility Based on the CORINE Model in the Gumara-Maksegnit Watershed, Ethiopia - Gurebiyaw, Kassaye; Kendie Addis, Hailu; Teklay, Achenafi (JNRD - Journal of Natural Resources and Development, 2018)
Soil erosion is one of the major environmental threats in the northwestern Amhara Region of Ethiopia. The objective of this study is to assess the spatial heterogeneity of soil erosion risk within the Gumara-Maksegnit watershed (57.3 km2) using the Coordination of Information on the Environment (CORINE) soil erosion assessment method to determine the most endangered areas. The model is simple and robust and consists of six steps overlaying combinations of soil texture, depth, stoniness, climatic and land-use/land-cover information with GIS support. The CORINE model was used to produce potential and actual soil erosion maps. The potential soil erosion map consists of the erosion risk of the land without considering current vegetation, but can be expanded to consider current land cover. The potential soil erosion risk map showed that a small part of the watershed (6.63 %) had low risk, 17.92 % had moderate risk and a large part of the study area (75.45 %) had high potential erosion risk. Meanwhile, the actual soil erosion risk map showed that a small part of the watershed (11.92 %) had low risk, 20.85 % of the area had moderate risk, and a large part of the study area (67.23 %) had high actual soil erosion risk. Low soil erosion risk areas were located in the southern part of the watershed, high erosion risk areas were found in the northern, northwestern and eastern part of the watershed, while moderately risky areas were randomly distributed throughout the watershed. Overall, the CORINE model can play a role in soil and water conservation by identifying highly endangered areas.
Keywords: Actual erosion risk; Climate, GIS; Potential erosion risk; Soil erosion